The Mysterious Disappearance of the Fountain: An exploration of changing pseudo-public spaces through the lens of fountains - Tinna Martinsdóttir 2001- (2022)
This thesis seeks to examine the stories and removal of two fountains in Reykjavík that existed within pseudo-public spaces. Pseudo-public spaces are spaces that appear public yet are private. The fountains in question were located within Kringlan shopping center and Perlan – a cultural center. Although these spaces are known to be privately run, there is an element of publicness that exists within them; i.e. shopping streets within a mall and the marketplace that used to be present in Perlan. The research heavily depended upon newspaper articles, photographic databases, and journals. The thesis explores the fountain removal in context with a broader transformation of pseudo public spaces: evolving from embodying a civic quality to becoming almost entirely commercialized.